(untitled) (Journal of Kidney Cancer, 2024)
Germ cell tumor (GCT) is a neoplasm typically found in childhood, commonly originating from the testis or ovary. While there have been reported cases of GCT occurring in various extragonadal sites, primary intrarenal GCT is exceptionally rare. We present a case of 37-year-old male who presented with right upper abdomen pain. Imaging revealed a sizable mass within the right kidney. The patient underwent surgical resection of the renal mass during which there was perirenal infiltration into the duodenum and dense desmoplastic reaction all around. Subsequent histopathology confirmed the diagnosis of primary intrarenal nonseminomatous germ cell tumor (NSGCT). The patient underwent four cycles of adjuvant bleomycin, etoposide, and cisplatin (BEP) chemotherapy; at 6 months of follow-up, he is fine. The objective of this case report is to underscore the importance of considering NSGCT as a potential rare differential diagnosis in cases of renal neoplasms and further plan for the management.